South Africa’s Weekly Media: Front-Page Reporting 9/11, Preventing Islamophobia - Muhammed Haron (Journal for the Study of Religion)
New York’s twin tower bombings, popularly referred to as 9/11, are regarded as a watershed period in world affairs. It happened at the cusp of the new century and its impact, since then, has been enormous, for it radically changed many aspects of human life. Both the print and the electronic media were pivotal in these changes. Besides shaping the way that communities perceive others, it also influenced the manner in which communities are dealing with one another. Since a radical Muslim group was blamed for this dastardly deed and since Muslims were implicated for this reprehensible act, the secular media expectedly placed the Muslims – in majority and minority settings – around the world under the spotlight. The media’s negative portrayal and reporting about Muslims did not only contribute towards a tendentious relationship between the media and the Muslims but it also contributed towards the spread of Islamophobia. This thus caused Muslims in both majority and minority settings to adopt a skeptical view of the role of the secular media. Considering these developments, this essay’s focus turns to the South African print media that reported and analyzed their reporting of this event during that period. Since it is beyond this essay’s scope to look at all the country’s daily and weekly tabloids, it restricted itself to two widely circulated South African weekly newspapers, namely the Sunday Times and Mail & Guardian. It first describes and discusses their front-page reports as they captured the tragic 9/11 event, before it reflects on their editorials –columns providing one with insights into the respective editors’ understanding of this event and their perceptions of Muslims nationally and globally. Being a purely textual study, it conceptualizes Islamophobia as the essay’s conceptual frame.